Cumulative Intracranial Tumor Volume Augments the Prognostic Value of Diagnosis-Specific Graded Prognostic Assessment Model for Survival in Patients with Melanoma Cerebral Metastases. Issue 2 (4th August 2017) - Hirshman, Brian R; Wilson, Bayard R; Ali, Mir Amaan; Schupper, Alexander J; Proudfoot, James A; Goetsch, Steven J; Carter, Bob S; Sinclair, Georges; Bartek, Jiri; Chiang, Veronica; Fogarty, Gerald; Hong, Angela; et al.
Abstract: BACKGROUND: The diagnosis-specific graded prognostic assessment scale (ds-GPA) for patients with melanoma brain metastasis (BM) utilizes only 2 key prognostic variables: Karnofsky performance status and the number of intracranial metastases. We wished to determine whether inclusion of cumulative intracranial tumor volume (CITV) into the ds-GPA model for melanoma augmented its prognostic value. OBJECTIVE: To determine whether or not CITV augments the ds-GPA prognostic scale for melanoma. METHODS: We analyzed the survival pattern of 344 melanoma patients with BM treated with stereotactic radiosurgery (SRS) at separate institutions and validated our findings in an independent cohort of 201 patients. The prognostic value of ds-GPA for melanoma was quantitatively compared with and without the addition of CITV using the net reclassification index (NRI > 0) and integrated discrimination improvement (IDI) metrics. RESULTS: The incorporation of CITV into the melanoma-specific ds-GPA model enhanced its prognostic accuracy. Addition of CITV to the ds-GPA model significantly improved its prognostic value, with NRI > 0 of 0.366 (95% CI: 0.125-0.607, P = .002) and IDI of 0.024 (95% CI: 0.008-0.040, P = .004). We validated these findings that CITV improves the prognostic utility of melanoma ds-GPA in an independent cohort of 201 melanoma cohort. CONCLUSION: The prognostic value of the ds-GPA scale for melanoma BM is enhanced by the incorporation of CITV.